Mauritius Royal Alfred Observatory parallel temperature measurements 1884-1903, original file in °Fahrenheit - Peter W Thorne (PANGAEA, 2021)
A suite of parallel meteorological measurements were undertaken over the extended period 1884-1903 at the Royal Alfred Observatory in Mauritius. The data were observed in: a well-ventilated room, by means of a Thermograph in a dedicated building, in a Stevenson Screen and by a Hygrometer in a different Stevenson Screen both in an enclosure, and for a short period two additional Stevenson Screens. Data were recorded in a series of annual reports from the observatory - two forms of which were produced each year. However, only a subset of these reports have been found. Data have been transcribed as monthly summaries of maximum, minimum, average (of certain hours) and mean (of max/min). The latter have been computed from max and min where not directly reported. All values are in the originally reported Fahrenheit values. Data were transcribed for a masters thesis by Samuel Awe and supplemented by subsequent transcriptions by Peter Thorne.